Interactions 1 - Linda R. Baker (McGraw-Hill, 2003)
The content and themes found in the new Integrated Skills Editions are based on materials from the highly successful Interactions series. Like its parent series, the Integrated Skills Program places a great emphasis on the development of skills and strategies in all language areas. All of the reading selections found in the Interactions Integrated Skills Editions, are fresh and new, with a wide variety of formats and themes